Entrepreneurial Self-Efficacy and Venture Success of Manufacturing Firms in Rivers State, Nigeria - Ajuka, Humphrey Monday; Letam, Noble Sordum; Gbarakae, Sampson Godae (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2024)
Manufacturing firms in Rivers State were the focus of this research, which aimed to assess their entrepreneurial self-efficacy and venture success. With government policy serving as the moderating variable, the dimensions of self-efficacy included accomplishment orientation, idea creation, and resilience. The indicators of venture success included financial success, market success, and operational success. The researchers in this study mostly used a survey research strategy based on correlations. Based on data collected from the Manufacturers Association of Nigeria, Rivers state branch, this study's population consists of 294 management workers from 98 manufacturing enterprises in Rivers state. This study used the taro yamen sampling formula with a sample size of 170. We used a structured questionnaire to gather our data. Items are dependable according to Cronbach's Alpha, which showed a dependability index of.874. You can see the responder demographics in the bar chart. We analyzed the study variables using descriptive statistics, which include means and standard deviations. To test our hypotheses, we used the Spearman Rank Order Correlation Coefficient with a significance threshold of 0.05. In order to examine the government policy controlling variable, we used the partial correlation. The study found that manufacturing firms in Rivers state that are achievement oriented are more likely to have ventures that are successful, that manufacturing firms in Rivers state that are resilient are more likely to have ventures that are successful, and that there is a significant relationship between idea generation and venture success. In Rivers state, entrepreneurial self-efficacy is a major factor in the success or failure of industrial businesses. It has an effect on the businesses' overall performance and sustainability by affecting accomplishment orientation, idea creation, and resilience. Findings from the research suggest that manufacturing companies may encourage a growth mindset among their workers by outlining specific, attainable goals that contribute to the overall purpose and vision of the company.